2017
DOI: 10.1021/acsami.7b01185
|View full text |Cite
|
Sign up to set email alerts
|

Oxidase Activity of the Barnacle Adhesive Interface Involves Peroxide-Dependent Catechol Oxidase and Lysyl Oxidase Enzymes

Abstract: Oxidases are found to play a growing role in providing functional chemistry to marine adhesives for the permanent attachment of macrofouling organisms. Here, we demonstrate active peroxidase and lysyl oxidase enzymes in the adhesive layer of adult Amphibalanus amphitrite barnacles through live staining, proteomic analysis, and competitive enzyme assays on isolated cement. A novel full-length peroxinectin (AaPxt-1) secreted by barnacles is largely responsible for oxidizing phenolic chemistries; AaPxt-1 is drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(98 citation statements)
references
References 52 publications
7
91
0
Order By: Relevance
“…As previously mentioned, barnacle cement does not contain DOPA;10, 11, 12 however, Gohad et al and Dickinson et al demonstrated that cyprid cement and the barnacle cementing apparatus are phosphorylated, respectively 14, 30. Likewise, we observe that the cyprid adhesive plaque ( Figure 4 a), cuticular tissues, and some surface deposits positively stain for phosphorylation (Figure 4b).…”
supporting
confidence: 77%
“…As previously mentioned, barnacle cement does not contain DOPA;10, 11, 12 however, Gohad et al and Dickinson et al demonstrated that cyprid cement and the barnacle cementing apparatus are phosphorylated, respectively 14, 30. Likewise, we observe that the cyprid adhesive plaque ( Figure 4 a), cuticular tissues, and some surface deposits positively stain for phosphorylation (Figure 4b).…”
supporting
confidence: 77%
“…Elastin is insoluble, and rich in hydrophobic amino acids, such as glycine and proline, which form mobile hydrophobic regions bounded by crosslinks between lysine residues [26]. Thus, elastin has been associated with a cross-linking mechanism of bulk proteins in the cement [10].…”
Section: The Proteome Profile Of Pollicipes Pollicipes Cement Glandmentioning
confidence: 99%
“…This model has been updated in the last years [10][11][12], including the notion that surface coupling relies on catechol groups, through various adhesive and cohesive forces, and that catechol, quinone, and lysine-based cross-linking are also involved in protein nanofibers' curing and proper holdfast to the adhesion surface [10]. However, in barnacles, the catechol groups responsible for β-amyloid fibrils' cross-linking of bulk proteins do not have a peptidyl origin, differently from other marine organisms, e.g., mussels and sandcastle worms; non-peptidyl catechol precursors and lysine are incorporated among bulk cement protein (CP52k and CP100k) fibrils through enzymatic reactions that involve peroxidases and lysyl oxidase [10], providing structure and mechanical characteristics to the composite. Six barnacle-specific cement proteins (CPs) have been identified, four of which are thought to be interface proteins, CP19k, −20 k, −43 k, and −68 k, and two bulk proteins, CP52k and CP100k, [13].…”
Section: Introductionmentioning
confidence: 99%
“…Three predicted proteins identified in peptide sequences from D. triton egg sacs are homologous to peroxidases. Peroxidases belong to a family of heme-containing enzymes that are involved in diverse biological roles such as peroxidase-catalysed protein cross-linking in barnacle cement (So et al, 2016(So et al, , 2017 and mosquito egg chorion layer (Li et al, 1996;Li and Li, 2006). A peroxidase has also been identified in the major and minor ampullate silk glands of the orb-web weaver Nephila senegalensis; this enzyme (NsPox) is thought to contribute to the initiation of disulphide links in outer layer silk proteins during fibre processing (Vollrath and Knight, 1999;Pouchkina et al, 2003).…”
Section: Electron Microscopy and Proteomics Of D Triton Egg Sac Silkmentioning
confidence: 99%